1997
DOI: 10.1021/la960700a
|View full text |Cite
|
Sign up to set email alerts
|

Growth Mode Transition Involving a Potential-Dependent Isotropic to Anisotropic Surface Atom Diffusion Change. Gold Electrodeposition on HOPG followed by STM

Abstract: The electrodeposition of gold on highly oriented pyrolytic graphite (HOPG) from acid aqueous solutions was studied by using electrochemical techniques complemented with ex-situ scanning tunneling microscopy (STM). The kinetics of gold electrodeposition is consistent with a nucleation and three-dimensional growth process under diffusion control from the solution side. As the applied potential moves in the negative direction, the gold crystal density increases, and the crystal shape changes from a Euclidean to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 33 publications
5
88
1
Order By: Relevance
“…The conventional routes utilize methods involving deposition of vaporized atoms from the gas phase, or reduction of their salts using electrochemical and/or electroless wet chemical methods. Other unconventional techniques utilizing lasers, ion-beams and Xrays have also been investigated for incorporating metal clusters on to the substrates in the desired chemical and morphological state(s) [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Use of energetic particle beams and X-rays are particularly attractive since clean lithographic techniques can also be introduced for direct-writing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional routes utilize methods involving deposition of vaporized atoms from the gas phase, or reduction of their salts using electrochemical and/or electroless wet chemical methods. Other unconventional techniques utilizing lasers, ion-beams and Xrays have also been investigated for incorporating metal clusters on to the substrates in the desired chemical and morphological state(s) [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Use of energetic particle beams and X-rays are particularly attractive since clean lithographic techniques can also be introduced for direct-writing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Pd-Fe and Au interaction, the current-time transient shows a sharp drop in the initial current density due to the charging of the double layer, which was followed by a nonlinear increase in the current density with electrodeposition time. Such double layer charging was also observed during the electrodeposition of various metals [29][30][31][32][33]. The elec- trodeposition kinetics of Pd-Fe on the Au electrode in the AAO template, decreasing and then beginning to increase the current density, occurred over a very short time period.…”
Section: Resultsmentioning
confidence: 73%
“…The observed increasing roughness of the gold deposits when the applied potential is moved to the negative direction is in agreement with the results of Martin et al about the electrodeposition of gold from acid aqueous solutions. 19 It was shown that dendritic aggregates are produced when the gold surface is negatively charged at potential less than the potential of zero charge. The authors claimed that such growth behavior results from the anisotropic corner surface diffusion caused by the varying energy barriers for the diffusion of surface atoms at step edges, as has been observed for metal deposition from vapor.…”
Section: Electrodeposition Of Gold Filmsmentioning
confidence: 99%